Application Elimination Et Choix Traduisant La REalité (ELECTRE) On Decission Support System - Agusta Praba Ristadi Pinem; Prind Triajeng Pungkasanti (Jurusan Teknologi Informasi Universitas Semarang, 2018)
Technology as a learning material will impact students impact in the future, in certain and details lesson material. Decission Support System teach how to solve the problems with algorythm methods application. One of them is ELimination Et Choix Traduisant la REalité (ELECTRE). ELECTRE is a complex methods with various stages in solving problems. ELECTRE is difficult to understand in convensional way. Furthermore, this research aimed to solve the problems by create experimental tool called ELECTRE application.